The search for the accomplishment of the preventive examination of cancer cytology: a qualitative study - Ana Carolina B Lucarini; Claudinei José G Campos (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The examination of cancer cytology is an important tool in the prevention of the womb colon cancer. In this clinical-qualitative study it was objectified to identify and to analyze the psychosocial and cultural aspects that involve the search for the accomplishment of the examination of cancer cytology. Developed with users of a basic unit of health of the city of Campinas, between in the age range of the 20 to the 32 years. The analysis of the data became by means of the method of content analysis, using a process of categorize not prior . The following categories had been mentioned: social constructions between spoken and the lived one for the young adult women; motivation for accomplishment of the preventive examination; involved psychosocial and cultural aspects in the accomplishment and the expectation of the result of this examination; the professional link of the health and customer in the search for the prevention; level school and religion: its influence in the search for the prevention. We conclude that involved the psychosocial and cultural aspects in the accomplishment of this examination are innumerable, differing in accordance with its social insertion, level school, cultural taboos. Independent of the age range, the question of the sicken possibility functions as encourage factor for prevention, however the social construction between spoken and the lived one for these women are very conflicting when it mentions to the possibility of accomplishment and regularity of the preventive examination.